(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2019)
This article arises from certain questions about the popular becoming of feminisms in Argentina. Drawing on the research interest about this process which has been understood as the successful construction of a “feminist people”, we focus on what we consider to be the central conditions that made possible the popular becoming of feminism. Starting from recognizing the genealogy of activism in the country, we look at the singular relationship of feminisms with human rights activism. Later on, we focus on the effects of displacement and contamination resulting from the linkage between kirchnerism and the human rights movement, as a process of populist articulation that we understand affected decidedly - and not, voluntarily- political identifications within feminisms.